A history of the theatre laboratory - Brown, Bryan Keith, 1976- (Routledge, Taylor & Francis Group, 2019)
"The term 'theatre laboratory' has entered the regular lexicon of theatre artists, producers, scholars and critics alike. And yet, use of the term is far from unified, often operating as an catch-all for a web of intertwining practices, territories, pedagogies and ideologies. Russian theatre, however, has seen a clear emergence of laboratory practice that can be divided into two distinct organisational structures: the studio and the masterskaya (artisanal guild). By assessing these structures, Bryan Brown offers two archetypes of group organisation that can be applied across the arts and sciences, and reveals a complex history of the laboratory's characteristics and functions that support the term's use in theatre. This book's discursive, historical approach has been informed substantially by contemporary practice, through interviews with, and examinations of, practitioners including Slava Polunin, Anatoli Vassiliev, Sergei Zhenovach and Dmitry Krymov"--